Design of Corrugated Airfoil for a Flapping Wing Micro Air Vehicle - Syed Hossein Raza Hamdani; Fatima Tuz Zehra; Muhammad Umer Sohail; Hassan Elahi; Muhammad Rizwan Mughal (International Journal of Aerospace Engineering)
The design of micro air vehicles (MAVs) presents unique challenges, particularly in achieving efficient aerodynamic performance and maneuverability within strict size and weight constraints. Flapping wing MAVs, inspired by nature’s efficient flyers, offer promising solutions but demand innovative approaches to aerodynamic design. Bioinspired flapping wing MAVs are the latest research area in the development of aviation technology and find their application in vast fields like military, government, and research institutes and for commercial purposes. The corrugated airfoil concept draws inspiration from natural fliers such as birds and insects, where corrugated wing structures contribute to improved aerodynamic efficiency and robustness. A new wing design approach has been proposed to be used for a flapping wing MAV, operating at lower Reynolds number regime that offers equally good or minimally compromised aerodynamic performance as compared to the previously used wing design with increased structural strength. This design approach is based on inducing regular corrugations (or surface perturbations) on a smooth elliptical airfoil. Using the National Advisory Committee for Aeronautics 0012 airfoil as a baseline, a parametric study has been conducted for the design parameters of the corrugations. Two different motions for the designed airfoils have been studied, including the pitching motion of airfoil through a constant free stream and impulsively started translation motion. The pitching motion has been studied at three different reduced frequencies, and the impulsively started translation motion has been studied for two acceleration modes, that is, fast acceleration and slow acceleration. The study also compares the aerodynamic efficiencies of smooth and corrugated airfoils during these motions. Reynolds number sensitivity analysis is also performed to study the behaviour of these airfoils at different Reynolds number flight regimes. Finally, a structural strength analysis is conducted to analyze the expected structural advantages this new design approach offers. Results demonstrate the superiority of the corrugated airfoil design compared to traditional airfoils in terms of lift generation, stall resistance, and maneuverability. Furthermore, insights gained from this study contribute to advancing the understanding of aerodynamic principles underlying flapping wing flight and pave the way for future developments in MAV design and optimization.